RHEOLOGICAL PROPERTIES AND BEARING CAPACITY OF FROZEN SOILS (RHEOLOGICHESKIE SVOISTVA I NESUSHCHAIA SPOSOBNOST' MERZLYKH GRUNTOV) - Vailov, S. S. (1965)
The rheological properties of frozen soil caused by the presence of ice and non-frozen water are important factors, without consideration of which calculations of the stability and steadiness of frozen soil are not possible. In the present work certain principles of rheology and the stability of frozen soil were examined, and proceeding from these principles an evaluation of the bearing capacity of natural footings and artificial pile foundations was made. Trans. of USSR document dated 1959.